2020
DOI: 10.3390/antibiotics9090605
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Multiple Impacts of Furfural Acetone on Nematodes In Vitro and Control Efficiency against Root-Knot Nematodes in Pots and Fields

Abstract: Root-knot nematodes (RKNs) seriously endanger agricultural development and cause great economic losses worldwide. Natural product furfural acetone (FAc) is a promising nematicide with strong attractant and nematicidal activities, but baseline information about the impact of FAc on the reproduction, egg hatching, feeding, and growth of nematodes and its pest control efficiency in field are lacking. Here, the inhibition effects of FAc on nematodes in vitro and its RKN control efficiency in pot and field were inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 44 publications
1
7
0
2
Order By: Relevance
“…7%) of avermectin at a dose of 1 mg/pot (Figure 1B). These results were consistent with previous studies [18,19], indicating the stable RKN control efficiency of FAc.…”
Section: Efficiency Of Fac Against M Incognita In Potssupporting
confidence: 94%
See 3 more Smart Citations
“…7%) of avermectin at a dose of 1 mg/pot (Figure 1B). These results were consistent with previous studies [18,19], indicating the stable RKN control efficiency of FAc.…”
Section: Efficiency Of Fac Against M Incognita In Potssupporting
confidence: 94%
“…FAc was also found to have reproductive inhibition activity on nematodes (Figure 2). Unlike other nematicides with only single nematicidal activity, FAc has various anti-nematode activities, including attract-and-kill effect [18] and inhibition activity of egg-hatching, feeding, and growth [19]. FAc has been proven to inhibit nematodes in all life stages, which can explain why it exhibited a control effect in fields equivalent with those of the commercial nematicides avermectin and metam sodium [19].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These results demonstrated that FAc is an appropriate alternative for nematicide development. 234 Gymnoascole acetate was previously isolated as a nematicidal component of the fungal strain G. reessii za-130. In pot experiments on tomato plants, the numbers of root galls in plants and M. incognita within both soil and roots were markedly reduced following treatment with 2-200 mg mL −1 gymnoascole acetate per kg soil.…”
Section: Examples Of Natural Metabolites For Nematode Biocontrolmentioning
confidence: 99%